Incarcerated During a Pandemic: Implications of COVID-19 for Jailed Individuals and Their Families. Issue 5 (20th October 2022) - Charles, Pajarita; Muentner, Luke; Jensen, Sarah; Packard, Chiara; Haimson, Chloe; Eason, John; Poehlmann-Tynan, Julie
ABSTRACT: U.S. jails are typically over-crowded settings and have faced notable social distancing challenges and a lack of personal protective equipment during the COVID-19 pandemic. In response, institutions made swift policy changes that included canceling in-person visits, suspending programming, and releasing a proportion of people with low-level charges. That said, a still-significant number of individuals remained incarcerated for whom the consequences of such abrupt procedural changes amidst an ongoing pandemic remain largely unknown. To begin to examine this, 33 adults in a mid-sized, county jail were surveyed to assess their experiences. Participants were majority Black men, half of whom were parents, and all had been tested for COVID-19. Quantitative and qualitative data were collected yielding results, which indicated that COVID-19 significantly disrupted daily jail activities, adversely influenced health, and strained family relationships. Use of segregation, delayed court proceedings, inadequate health responses, and suspended programming and visits with limited contact alternatives reportedly intersected with depleted mental health to contribute to feelings of isolation and heightened concern for the well-being of family. Policy and practice implications are discussed that would help incarcerated people receive necessary support and maintain family connections while mitigating health concerns that emerge during public health crises.